Design and test of synthetic jet actuator for small UAVS - Du, Jiaxing. (2012)
In this project synthetic jet actuators based on piezoelectric ceramic unimorph are designed and fabricated. Tests are done in both quiescent and crossflow conditions, results show that actuator performance depends on orifice location and actuation frequency. Besides flow visualization demonstrates actuators’ capability to suppress flow separation on LS (1)-0421 wing model. This lays the foundation for its potential application on unmanned aerial vehicle.